Distinctive Structural and Non-Structural Building Defects and Failures in Educational Buildings - Tan, Sin Wen; Othuman Mydin, Md Azree (Eftimie Murgu University of Resita, 2013)
Although the maintenance-free building may be a theoretical possibility, all buildings are subject to the vagaries of defects, failures, deterioration and variation. The examples of these problems are fungus growth, peeling paint, termite attack, dampness, defective rainwater goods, roof defects, harmful growth, settlement, foundation failure, roof collapse and others. There are a great number of building defects and failures arose and being reported officially by mass media, especially problems with educational buildings. Theoretically, all buildings tend to deteriorate over period of time due to aging or other factors, regardless the types of buildings. There are several main factors can be taken into account such as design fault, poor maintenance, poor workmanship, building age and location of building. This paper will discuss on distinctive structural and non-structural building defects and failures than frequently happened in educational buildings. This paper is noteworthy to render varies of problems generally faced by Malaysian educational buildings to the public. As such, the awareness among them can be raised or improved. Furthermore, the public will concern, especially the government authorities should emphasize the laws and regulations to enforce the safety of construction work as well as the procedure in giving approval to the occupation of educational buildings.